Perancangan Pengontrol Otomatis dan Pengatur Posisi Tempat Duduk pada Kursi - Fahrozi, Fikri (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2020)
A wheelchair is a tool used by people who have difficulty walking due to illness, injury or disability. This tool can be driven by being pushed by someone else, moved by using a hand, or by using an automatic machine. To support the development in the world of health, it is necessary to have technological innovations in wheelchair products to increase user convenience and comfort. The purpose of this paper is to provide ideas and innovative contributions in the form of automatic control in a wheelchair. The methodology applied includes the design, manufacture, testing, and selection of components for the automatic controller and seat position control in a wheelchair.